Pengembangan Media Bimbingan Dan Konseling Berbasis Podcast Persiapan Karir - Sakerebau, Desti Marnida; Berdikariyanto, Esrabella Putri Maharani; Windrawanto, Yustinus; Agustin, Adhi Krisna Maria (Guidance : Jurnal Bimbingan dan Konseling, 2025)
This study aims to develop guidance and counseling media, especially media as a form of interaction in improving student understanding and the skills of BK teachers in delivering material to students. The background of this study is that many students are still confused in determining career choices. The method used in this study is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The final product is a podcast "Career Preparation" which consists of several episodes and has gone through expert validation tests and limited trials. The validation results show that this media is in the "very feasible" category with a feasibility percentage above 81%. The results of the limited trial also showed positive responses to the content, delivery, audio-visual quality, and benefits of the material. In conclusion, this podcast media is worthy as an alternative career guidance service that is easily accessible and in accordance with the needs of today's students. Keywords: career guidance, podcast media, career planning, ADDIE, career readiness Penelitian ini bertujuan untuk mengembangkan media bimbingan dan konseling khususnya media sebagai bentuk interaksi dalam meningkatkan pemahaman siswa serta keterampilan guru BK dalam menyampaikan materi kepada peserta didik. Latar belakang penelitian ini adalah banyaknya peserta didik yang masih mengalami kebingungan dalam menentukan pilihan karir. Metode yang digunakan dalam penelitian ini adalah Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Produk akhir berupa podcast “Career Preparation” yang terdiri dari beberapa episode dan telah melalui uji validasi ahli serta di uji coba terbatas. Hasil validasi menunjukkan media ini berada dalam kategori “sangat layak” dengan persentase kelayakan di atas 81%. Hasil uji coba terbatas juga menunjukkan tanggapan positif terhadap isi, penyampaian, kualitas audio-visual, serta manfaat materi. Kesimpulannya, media podcast ini layak sebagai alternatif layanan bimbingan karir yang mudah diakses, dan sesuai dengan kebutuhan peserta didik masa kini. Kata Kunci: bimbingan karir, media podcast, perencanaan karir, ADDIE, kesiapan karir